Effects of l-Carnitine, Erythritol and Betaine on Pro-inflammatory Markers in Primary Human Corneal Epithelial Cells Exposed to Hyperosmotic Stress. (July 2015) - Hua, Xia; Su, Zhitao; Deng, Ruzhi; Lin, Jing; Li, De-Quan; Pflugfelder, Stephen C.
Abstract Purpose: To explore the effects of osmoprotectants on pro-inflammatory mediator production in primary human corneal epithelial cells (HCECs) exposed to hyperosmotic stress. Methods: HCECs cultured in iso-osmolar medium (312 mOsM) were switched to hyperosmotic media with or without prior incubation with 2–20 mM of l-carnitine, erythritol or betaine for different time periods. The mRNA expression and protein production of pro-inflammatory markers in HCECs were evaluated by RT-qPCR and ELISA. Results: Hyperosmolar media significantly stimulated the mRNA and protein expression of pro-inflammatory cytokines, TNF-α, IL-1β and IL-6, and chemokines, IL-8, CCL2 and CCL20 in HCECs in an osmolarity dependent manner. The stimulated expression of these pro-inflammatory mediators was significantly but differentially suppressed by l-carnitine, erythritol or betaine. l-Carnitine displayed the greatest inhibitory effects and down-regulated 54–77% of the stimulated mRNA levels of TNF-α (down from 12.3–5.7 fold), IL-1β (2.2–0.9 fold), IL-6 (7.3–2.9 fold), IL-8 (4.6–2.0 fold), CCL2 (15.3–3.5 fold) and CCL20 (4.1–1.5 fold) in HCECs exposed to 450 mOsM. The stimulated protein production of TNF-α, IL-1β, IL-6 and IL-8 was also significantly suppressed by l-carnitine, erythritol and betaine. l-carnitine suppressed 49–79% of the stimulated protein levels of TNF-α (down from 81.3 to 17.4 pg/ml), IL-1β (56.9–29.2 pg/ml), IL-6 (12.8–4.6 ng/ml) and IL-8 (21.2–10.9 ng/ml) by HCECs exposed to 450 mOsM. Interestingly, hyperosmolarity stimulated increase in mRNA and protein levels of TNF-α, IL-1β and IL-6 were significantly suppressed by a transient receptor potential vanilloid channel type 1 (TRPV1) activation inhibitor capsazepine. Conclusions: l-carnitine, erythritol and betaine function as osmoprotectants to suppress inflammatory responses via TRPV1 pathway in HCECs exposed to hyperosmotic stress. Osmoprotectants may have efficacy in reducing innate inflammation in dry eye disease.